2014
DOI: 10.1002/ijc.29368
|View full text |Cite
|
Sign up to set email alerts
|

Negative modulation of the epigenetic regulator, UHRF1, by thyroid hormone receptors suppresses liver cancer cell growth

Abstract: The thyroid hormone, 3,3 0 ,5-triiodo-L-thyronine (T 3 ), mediates several physiological processes, including embryonic development, cellular differentiation, metabolism and regulation of cell proliferation. Thyroid hormone (T 3 ) and its receptor (TR) are involved in metabolism and growth. In addition to their developmental and metabolic functions, TRs play a tumor suppressor role, and therefore, their aberrant expression can lead to tumor transformation. Aberrant epigenetic silencing of tumor suppressor gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 39 publications
1
34
0
Order By: Relevance
“…T3 binds to TR regulating the expression of various genes including those involved in cell proliferation [103]. In this context, it has been shown that T3 negatively regulates the expression of UHRF1 in hepatoma cell line, which highly overexpresses TRα1 [104]. UHRF1 was shown to be overexpressed in liver cancer patients and its overexpression was accompanied with the size of tumor [104].…”
Section: Signalling Pathways Involved In Uhrf1 Regulation In Cancer Cmentioning
confidence: 99%
See 3 more Smart Citations
“…T3 binds to TR regulating the expression of various genes including those involved in cell proliferation [103]. In this context, it has been shown that T3 negatively regulates the expression of UHRF1 in hepatoma cell line, which highly overexpresses TRα1 [104]. UHRF1 was shown to be overexpressed in liver cancer patients and its overexpression was accompanied with the size of tumor [104].…”
Section: Signalling Pathways Involved In Uhrf1 Regulation In Cancer Cmentioning
confidence: 99%
“…In this context, it has been shown that T3 negatively regulates the expression of UHRF1 in hepatoma cell line, which highly overexpresses TRα1 [104]. UHRF1 was shown to be overexpressed in liver cancer patients and its overexpression was accompanied with the size of tumor [104]. Exposure of TR-expressing HepG2 cells to T3 decreased the levels of UHRF1 mRNA and protein compared to TR-muted HepG2 [104].…”
Section: Signalling Pathways Involved In Uhrf1 Regulation In Cancer Cmentioning
confidence: 99%
See 2 more Smart Citations
“…31 Moreover, UHRF1 promotes proliferation and progression in many cancers, including colorectal, 8,9 bladder cancer 32 and liver cancer. 13,33 These results indicate that overexpression of UHRF1 is closely associated with tumor proliferation. Thus, we speculate that UHRF1 may enhance GC cell proliferation and tumorigenesis.…”
mentioning
confidence: 76%